Phase transformation and microstructure of wollastonite glass–ceramics in Na2O–CaO–SiO2 system under different heat treatment conditions. (July 2014) - Yao, S. Y.; Cao, H. X.; Wang, P.; Zhang, W. W.; Huo, W. L.; Xu, W.
<x content-type="archive" xml:space="preserve">Abstract</x> Wollastonite glass–ceramic was prepared by using a sintering method. The chemical compositions were in the wollastonite crystallisation primary field of the Na2O–CaO–SiO2 system. Effects of heat treatment conditions on phase transformation and microstructure evolution of wollastonite glass–ceramic in Na2O–CaO–SiO2 system were investigated using X-ray diffraction and scanning electron microscopy. The results showed that the plate-like devitrite (Na2Ca3Si6O16) crystals were firstly precipitated from the parent glass after heat treatment at 950°C and long strip shape wollastonite (α-CaSiO3) crystals appeared in the clearance of Na2Ca3Si6O16 at 1000°C. When the heat treatment temperature increased to 1050°C, the Na2Ca3Si6O16 peak disappeared and α-CaSiO3 became the single phase. Furthermore, the complete phase transformation from α-CaSiO3 to pseudowollastonite (β-CaSiO3) occurred at 1200°C. As the heat treatment temperature increased, the sample surface changed from 'convex' into 'concave'.